2003
DOI: 10.1037/1528-3542.3.3.284
|View full text |Cite
|
Sign up to set email alerts
|

Repressive and defensive coping during fear and anger.

Abstract: In this study, the relationship between repressive and defensive coping styles and somatovisceral responses as well as emotion self-reports were investigated in 2 situational contexts conceived to induce fear and anger. Anxiety (State-Trait Anxiety Inventory; L. Laux, P. Glanzmann, P. Schaffner, & C. D. Spielberger, 1981) × Defensiveness (Marlowe-Crowne Social Desirability Scale; D. P. Crowne & D. Marlowe, 1960) × Emotion (fear, anger) moderated regression analyses revealed that compared with baseline during f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 54 publications
4
53
1
Order By: Relevance
“…A number of studies reported discrepancies between low self-reported anxiety and autonomic measures indicating objectively high physiological arousal in repressors (Asendorpf & Scherer, 1983;Barger, Kircher, & Croyle, 1997;Derakshan & Eysenck, 2001;Newton & Contrada, 1992;Pauls & Stemmler, 2003;Weinberger et al, 1979). This similarity between findings in memory and emotion studies implies that the explicitness with which sensitive information is asked for reduces both repressors' emotional experience and memory.…”
Section: Discussionmentioning
confidence: 90%
“…A number of studies reported discrepancies between low self-reported anxiety and autonomic measures indicating objectively high physiological arousal in repressors (Asendorpf & Scherer, 1983;Barger, Kircher, & Croyle, 1997;Derakshan & Eysenck, 2001;Newton & Contrada, 1992;Pauls & Stemmler, 2003;Weinberger et al, 1979). This similarity between findings in memory and emotion studies implies that the explicitness with which sensitive information is asked for reduces both repressors' emotional experience and memory.…”
Section: Discussionmentioning
confidence: 90%
“…In this first attempt with the TNT paradigm, our use of a continuum approach (ISE) was motivated in part by the difficulty of carrying out the design with full counterbalancing within four groups, as well as by the literature on suppression and repressive coping that revealed no differences among the three categories of non-repressors (Barnier et al, 2004;Geraerts et al, 2006). In general, continuum methods, like the fourcategory method, have consistently demonstrated that repressors report low anxiety while simultaneously exhibiting high levels of physiological arousal (e.g., Coifman, Bonanno, Ray, & Gross, 2007;Pauls & Stemmler, 2003). On the other hand, Derakshan, Myers, Hansen, and O'Leary (2004) found that defensiveness alone predicted spontaneous, uninstructed suppression of thoughts about an emotionally negative film, regardless of anxiety levels.…”
Section: Discussionmentioning
confidence: 99%
“…fear and anxiety evoked by the speech preparation paradigm, are followed by decreases in VT (Pauls & Stemmler, 2003). On the other hand, in research conducted by different authors (e.g.…”
Section: Introductionmentioning
confidence: 94%